Profil Rasul Paulus Dalam Surat 1 Korintus Dan Relevansinya Bagi Hamba-Hamba Tuhan Di Gereja Pantekosta di Indonesia Rungkut Surabaya - Julianus Zaluchu (Jurnal Teologi dan Pelayanan Kerusso, 2019)
The profile of God's servants is a very important teaching that God has entrusted to His church on this earth. God's servants often face enormous challenges in delivering the teachings of God's Word. Such as offers to compromise, participate in committing crimes, unhealthy ambitions to gain a position, engage in the business world and materialism. In the use of wisdom it is not uncommon for God's servants to make their own decisions without involving God. In terms of ethics, God's servants experienced a fall by the temptation of wealth, throne and women. There is even a servant of God directly involved in business and politics so that it deviates far from the teachings of God's Word. Many of God's servants consider it more powerful and pretend to know because they have many congregations, and have spiritual gifts such as speaking in tongues. To get maximum results, in this study the authors used qualitative research methods, historical research methods and descriptive research methods. Qualitative research methods by distributing questionnaires to congregants and to several servants of God who serve in the GPdI Rungkut church. This study collected data from the results of the distribution of questionnaire sheets to 175 eligible congregations to fill them. The conclusions of this research are 1) The Apostle Paul is a servant of God who was called by God to carry out His mission, which is to preach the gospel of Jesus Christ to all people; 2) First Corinthians describes the profile of the apostle Paul as a servant of God; 3) The Apostle Paul as a servant of God should be emulated by God's servants in Indonesia in general and in particular God's servants in the GPdI Rungkut Surabaya church; 4) God's servants must have knowledge about the profile taught by the apostle Paul so that they have a humble attitude, that is, an attitude that is not defensive when faced with resistance and a sincere attitude to help others; 5) Servants of God serve willingly and not accentuate their ministry so that praise is given from God not from humans; and 6) Servants of God have integrity and strict adherence to the spiritual laws contained in God's word.